Comparative Criminology and Criminal Justice within the African Continent (Strathmore Law Journal, 2022)
There is no corner of the world where crime cannot be found. Increasingly, conventional crimes are being compounded by transnational crimes which know no borders. Concern for public safety and security nationally, regionally, and internationally have increasingly becoming an international issue and concern. This has been reflected in the 16th of the United Nations Sustainable Development Goals (i.e., Peace, Justice, and Strong Institutions). There is an ever-increasing need for comparative criminology and criminal justice research in a world where communication, travel, and international cooperation and collaboration are becoming increasingly common. While many criminology and criminal justice programs offer related programs and courses, the practice of comparative criminological or criminal justice research on the African continent is less well developed. This article draws on existing research and practices to explore the rationale and justification for engaging in such research and offers several methodological approaches that can be used to promote comparative criminological and criminal justice inquiry and research within the African continent.